The Psychometric Properties of the Norwegian version of Inventory of Life Quality in Children and Adolescents (ILC) - Kristensen, Hanne; Thomsen, Per Hove (PsykTestBarn, 2013)
Description: Inventory of Life Quality in Children and Adolescents (ILC) is a questionnaire measuring health related quality of life in children and adolescents (ages 6-18 years) with mental and somatic disorders, but can also be used in healthy subjects. The questionnaire exists in a parent and child version and consists of seven items (nine for patients) rated on a 1-5 scale. It takes 5-15 min minutes to complete the form. For children 6-11 years old, ILC is administered as an interview. The Norwegian translation by Thomas Jozefiak and Ulrich Linnemann (2012) is based on the original German ILC version developed by Mattejat and Remschmidt in 2006. The questionnaire may be used by physicians, psychologists, and other health professionals with relevant education including training in quality of life assessment and ILC. The Norwegian edition of ILC is available from Hogrefe Psykologförlaget AB. Literature search: A systematic literature search yielded 72 publications. Of these, five articles from four Norwegian studies were included; one school-based population study and three clinical studies. In addition, we included the Norwegian ILC manual. Psychometrics: There are Norwegian norms based on a representative sample of children and adolescents (ages 6-18 years) from the county of Sør-Trøndelag. Clinical comparison values are provided from CAMHS clinics in the same county. In addition to clinical validity, satisfactory validity is reported against another measure of quality of life and against a measure of depression. Regarding reliability, the internal consistency is acceptable to good, except for the self-report of the youngest children and the children in the clinical sample. Test-retest reliability was good for two cohorts of the school sample. Sensitivity for change was only measured in the population-based sample. Conclusion: There is limited documentation for the psychometric properties of the Norwegian version of the ILC. However, the existing studies are of good quality including satisfactory norms and measures of validity and reliability.